Antibacterial, antifungal, phytotoxic, and genotoxic properties of two complexes of AgI with sulfachloropyridazine (SCP): X-ray diffraction of [Ag(SCP)]n - Mosconi, Natalia Ester (2014)
We report the synthesis, characterization, antibacterial and antifungal activities, phytotoxicity, and genotoxicity of two new complexes of silver(I) with sulfachloropyridazine (SCP), one of which is heteroleptic with SCP and SCN- ligands (Ag-SCP-SCN), the other of which is homoleptic (Ag-SCP); furthermore, the crystal structure of the homoleptic complex is disclosed. The heterocyclic N atom nearest to the Cl atom and the Nsulfonamide atom could be coordination sites for the silver ion in the Ag-SCP-SCN complex. The Ag-SCP complex is a polymeric compound with metal-metal bonds, and the heterocyclic and sulfonamide N atoms are points of coordination for Ag I. Both complexes showed activity against all the tested bacteria, and in the cases of Escherichia coli and Pseudomonas aeruginosa, the action was better than that of SCP. In all cases, both silver-SCP complexes showed better antifungal activity than SCP, which was inactive against the tested fungi. Notably, the activity against P. aeruginosa, a nosocomial multidrug-resistant pathogen, was better than that of the reference antibiotic cefotaxim. Both silver-sulfa complexes displayed moderate activity against the tested yeast, especially for C. neoformans, which is an important fact considering the incidence of cryptococcosis, mainly in immune-deficient patients. No chromosomal aberrations were observed with the Allium cepa test, which is auspicious for further study of these complexes as potential drugs. Silver surfers: Two complexes of AgI with sulfachloropyridazine (SCP) were synthesized and characterized, and their antibacterial and antifungal activities, phytotoxicity, and genotoxicity were evaluated. Both complexes are more active than free SCP against bacteria and fungi. Neither complex shows cytotoxic effects or produces chromosome aberrations in the Allium cepa test.